Stratification and two glass-like thermal transitions in aged polymer films. Issue 43 (25th October 2017) - Pradipkanti, L.; Chowdhury, Mithun; Satapathy, Dillip K.
Abstract : Two glass-like thermal transitions and anomalous thermal expansion are observed in stratified and prolonged physically aged polystyrene films. Abstract : Using X-ray reflectivity, spectroscopic ellipsometry and Raman spectroscopy, we have studied the stratified structure and the two glass-like thermal transitions in sufficiently aged glassy polystyrene films. We find that favorable interaction between the solid substrate and the polymer film induces stratification within the film resulting in different densities across the film thickness. Existence of two glass-like thermal transitions (one at 70 °C and the other at 95 °C) is independently confirmed by temperature dependent spectroscopic ellipsometry and Raman spectroscopy measurements. Interestingly, the thermal coefficient of expansion of the polymer film displays anomalous behavior with temperature and is found to have the lowest value over the temperature range 70–95 °C, i.e. between the two observed glass-like thermal transition temperatures.